PENINGKATAN KAPASISTAS KONSELOR DALAM MENINGKATKAN PENGETAHUAN CALON PENGANTIN SEBAGAI UPAYA KEHAMILAN SEHAT UNTUK MENCEGAH STUNTING - Rina Julianti; Arpina Fajarnita; Nasrullah Nasrullah; Rikaoctriantiaskar Rikaoctriantiaskar; Evi Kristina (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
Stunting remains a public health problem that requires preventive measures starting from the preconception period. One of the strategic target groups in stunting prevention is prospective brides and grooms through increasing knowledge about healthy pregnancies. However, limited counselor capabilities in delivering material and the use of less engaging educational media are obstacles in the premarital counseling process. This Community Service (PkM) activity aims to increase the capacity of counselors in creating educational media and increasing prospective brides and grooms' knowledge about healthy pregnancies as an effort to prevent stunting. The activity was carried out at the Pusaka Johan Pahlawan KUA Office in West Aceh Regency through educational methods, training in creating educational media using Canva, hands-on practice, discussions, and pre-test and post-test evaluations. The activity targets 4 counselors and 30 prospective brides and grooms. The results of the activity showed an increase in the knowledge of prospective brides and grooms, with the average score (mean) increasing from 1.33 in the pre-test to 2.60 in the post-test, while the standard deviation changed from 0.63 to 0.70. Among counselors, the average knowledge score increased from 1.25 to 2.50, with a standard deviation of 0.50 to 0.58, after participating in the training. Furthermore, all counselors were able to create more engaging and communicative educational media to support premarital counseling. This activity has proven effective in increasing counselor capacity and prospective brides' knowledge regarding healthy pregnancies. These improvements are expected to support the optimization of premarital counseling services and contribute to accelerating the reduction of stunting rates through healthy pregnancy preparation from preconception.